Faculty development for teaching and evaluating professionalism: from programme design to curriculum change - Steinert, Yvonne; Cruess, Sylvia; Cruess, Richard; Snell, Linda (Medical education, 2005)
Introduction  The recent emphasis on the teaching and evaluation of professionalism for medical students and residents has placed significant demands on medicine's educational institutions. The traditional method of transmitting professional values by role modelling is no longer adequate, and professionalism must be taught explicitly and evaluated effectively. However, many faculty members do not possess the requisite knowledge and skills to teach this content area and faculty development is therefore required. Programme description  A systematic, integrated faculty development programme was designed to support the teaching and evaluation of professionalism at our institution. The programme consisted of think tanks to promote consensus and ‘buy‐in’, and workshops to convey core content, examine teaching strategies and evaluation methods, and promote reflection and self‐awareness. Programme evaluation  The programme was evaluated using a CIPP (context, input, process, product) analysis. The institution supported this initiative and local expertise was available. A total of 152 faculty members, with key educational responsibilities, attended 1 or more faculty development activities. Faculty participation resulted in agreement on the cognitive base and attributes of professionalism, consensus on the importance of teaching and evaluating professionalism, and self‐reported changes in teaching practices. This initiative also led to the development of new methods of evaluation, site‐specific activities and curriculum change. Discussion  A faculty development programme designed to support the teaching and evaluation of professionalism can lead to self‐reported changes in teaching and practice as well as new educational initiatives. It can also help to develop more knowledgeable faculty members, who will, it is hoped, become more effective role models.